Perbandingan Kombinasi Putih Telur Rebus Dan Ikan Gabus Dengan Pemberian Ikan Gabus Terhadap Penyembuhan Luka Sectio Cesarea Pada Ibu Nifas Di Rumah Sakit Ridhoka Salma Cikarang Barat - Nurhayati Binti Syafrudin; Resi Galaupa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Background: Maternal Mortality Rate (MMR) is a strategic indicator of health development that reflects the health status and quality of the population. The number of MMR in Indonesia in 2021 collected in the family health profile records at the Indonesian Ministry of Health still shows a high number of 7,389 deaths (RI Ministry of Health, 2022). Infection is one of the causes of maternal death, in developing countries at least one in ten maternal deaths is caused by infection. Postpartum wounds are still a common cause of infection in 80-90% of cases. Infections after childbirth are caused by normal birth wounds or caesarean section, mastitis, thrombophlebitis and pelvic inflammation. Objective: To determine the comparison of the combination of boiled egg white and snakehead fish with the administration of snakehead fish on the healing of cesarean section wounds in postpartum mothers. Methods: The design of this research is quantitative experimental research (quasi-experimental) with a